Quantum Dots, Particles, and Nanoclusters III 2006
DOI: 10.1117/12.641750
|View full text |Cite
|
Sign up to set email alerts
|

Quantum dot photonic crystal detectors

Abstract: In this paper we report the use of a photonic crystal resonant cavity to increase the quantum efficiency, detectivity (D*) and the background limited infrared photodetector (BLIP) temperature of a quantum dot detector. The photonic crystal is incorporated in InAs/InGaAs/GaAs dots-in-well (DWELL) detector using Electron beam lithography. From calibrated blackbody measurements, the conversion efficiency of the detector with the photonic crystal (DWELL-PC) is found to be 58.5% at-2.5 V while the control DWELL det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Most existing devices are realized as two-dimensional (2D) PC structures, as they are compatible with standard semiconductor processing. [24][25][26] PC crystal represents a regular array of holes (defects) that is used to modify the local refractive index to provide localized modes in the "photonic" band structure (see Fig. 10).…”
Section: Coupling Of Infrared Radiation With Detector-a New Perspmentioning
confidence: 99%
“…Most existing devices are realized as two-dimensional (2D) PC structures, as they are compatible with standard semiconductor processing. [24][25][26] PC crystal represents a regular array of holes (defects) that is used to modify the local refractive index to provide localized modes in the "photonic" band structure (see Fig. 10).…”
Section: Coupling Of Infrared Radiation With Detector-a New Perspmentioning
confidence: 99%
“…So, broadband absorption is usually inadequate due to quantum efficiency roll−off. To improve charge collection of photons with varying wavelengths application, the pho− tonic crystals to IR detectors are applied [31]. Krishna et al [32] have reported quantum efficiency improvement from 7% to 93% for reverse biased DWELL detector.…”
Section: Photon Trapping Detectorsmentioning
confidence: 99%
“…Photon trapping detectors have been demonstrated inde− pendently in II-VI and III-V based epitaxial materials [31][32][33][34]. Sub−wavelength size semiconductor pillar arrays within a single detector are designed and structured as an ensemble of 3D photonic structure units using either a top− −down or bottom−up process scheme to significantly in− crease absorption and quantum efficiency.…”
Section: Photon Trapping Detectorsmentioning
confidence: 99%